1994
DOI: 10.1038/ki.1994.177
|View full text |Cite
|
Sign up to set email alerts
|

Functional versus structural changes in the pathophysiology of acute ischemic renal failure in aging rats

Abstract: The aim of this study was to gain further insight into the greater susceptibility to acute ischemic renal failure (ARF, 30 min of renal arteries clamping) of old rats (O, 18 months) as against young rats (Y, 3 months). All the rats ate a hypoproteic diet (14% of casein) to avoid age-related glomerulosclerosis in O. Basal renal dynamics was similar in O and Y (Groups CON). One day after ARF, the decrease in GFR was more severe in O than in Y (-82% and -57% vs. respective CON, P < 0.05), due to a greater rise of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…Both Y and O rats were fed a moderately hypoproteic diet from birth (protein content, 14% as casein); previous studies in this laboratory have shown that such a diet delays the occurrence of age-related glomerulosclerosis while permitting a normal growth (3). After arriving at our facility, the rats were administered either the standard diet or a diet supplemented with ATO with free access to tap water for at least 14 d. The amount of ATO in the diet was calculated according to daily food intake of the rats to deliver about 15 mg/kg/d in Y rats and 12 mg/kg/d in O rats.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both Y and O rats were fed a moderately hypoproteic diet from birth (protein content, 14% as casein); previous studies in this laboratory have shown that such a diet delays the occurrence of age-related glomerulosclerosis while permitting a normal growth (3). After arriving at our facility, the rats were administered either the standard diet or a diet supplemented with ATO with free access to tap water for at least 14 d. The amount of ATO in the diet was calculated according to daily food intake of the rats to deliver about 15 mg/kg/d in Y rats and 12 mg/kg/d in O rats.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study from our laboratory has shown that ischemic injury after renal arteries clamping determines a more pronounced decrease of renal plasma flow (RPF) and GFR in old (O) rats when compared with young (Y) rats (3). Renal impairment in aging rats, however, was partially blunted by the administration of oral supplements of either arginine, the precursor of nitric oxide (NO), or SOD, a scavenger of reactive oxygen species (ROS), clearly suggesting that an endothelial dysfunction, secondary to NO deficiency and increased ROS production, was the main factor responsible for the intense renal vasoconstriction of aging animals (3).…”
mentioning
confidence: 99%
See 3 more Smart Citations